Professores da Educação Infantil (com formação em Educação Física): percepções e possibilidades sobre a BNCC e o arranjo curricular por campos de experiências - Diana, Fernando (2023)
The publication of the National Common Curriculum Base (BNCC), in December 2017, brought challenges to Early Childhood Education: one of them was to reflect on the ways to approach children's experiences in order to build a contextualized pedagogical practice full of meanings, both for the children and for the teachers themselves, within a curricular conception that differs from the other stages of basic education despite being integrated with them. The organization of this document raised questions: what would be the perception of Early Childhood Education teachers (with a background in Physical Education) about the BNCC for this stage of Basic Education? What do these teachers understand about the new proposition that has been introduced: the curricular arrangement by fields of experience? Is it possible for teachers with a specific degree (in the case of this study, in Physical Education) to work within this proposal? Starting from the hypothesis that there should be difficulties in understanding, either the BNCC itself as a document, or of the proposition of the idea of "curricular arrangement by fields of experience", considering that not even the document itself presents definitions or conceptualizations about the term, we propose this work aiming, by discussing the perception of the BNCC and the terms within it, especially those related to the idea of fields of experience, in the part of Early Childhood Education teachers (with a degree in Physical Education), to deepen the reflections on the conceptual organization of the BNCC for the stage of Early Childhood Education and propose possibilities of action, overcoming the logic of the schooling model, by thinking about it and making it effective as a space where conditions are created for educational experiences to happen, organized with the children, in which through interactions, play, observations, explorations, investigations, raising hypotheses, answers to questions and curiosities are sought. Hence, the work was organized in five chapters: Chapter 1 presents the history of Early Childhood Education and Brazilian School Physical Education, in a process of contextualization and understanding of how the past organizes and introduces the present; in Chapter 2, we discussed Early Childhood Education and Physical Education inserted in this stage of basic education today, addressing the implementation of the BNCC in our country, specifically in the Early Childhood Education stage, and presented reflections on Physical Education, as an area of knowledge, in this stage; Chapter 3 brings as the central axis of discussion the fields of experience, mainly from Finco (2015) and Fochi (2015; 2020), Dewey's ideas regarding the meaning and significance of the concept of experience, and the proposal and discussion of four principles as guiding axes for the organization of pedagogical practice by fields of experience: the principles of interaction, continuity, significance, and playfulness; the field research is in Chapter 4, presenting the methodological paths of qualitative research, the data collection by the Focus Group technique, its analysis from Bardin (2016) and the organization of Early Childhood Education in the city studied; Finally, Chapter 5 presents and discusses the categories of analysis extracted from the group's narrative and their respective units of record. The analysis of the data showed that we were right in our hypothesis that there were difficulties in understanding, either the BNCC itself as a normative document, or the proposition of the idea of curricular arrangement by fields of experience, since we are talking about a concept under construction and, as such, it is not finished for any teacher.